Non capisci cosa questo posto sia davvero? Narrativa seriale e logiche del racconto post-umano in Westworld - Vincenzo Del Gaudio (Funes)
The relationship between the narrative through which the notion of human is produced and its outside is increasingly at the center of a complex dialectic. This work aims to investigate the relationship between human and non-human, from a post-human perspective, through the representation that one of the most representative television series of the last few years produces. The TV series Westworld, produced by HBO and written by Jonathan Nolan and Lisa Joy, more than others gives us a complex narrative imagery through which to try to untangle the relationship between the anthropological machine (Agamben, 2002) that creates the human and its background. The narrative strategy of Westworld is to create a metanarrative space in which television neoseriality is presented on the one hand as a space for the production of the contemporary imaginary and on the other hand for the relationship betweenhuman and non-human, putting both narrative lines often together.